Effect of medroxyprogesterone acetate dose in progestin-primed ovarian stimulation on pregnancy outcomes in poor ovarian response patients with different body mass index levels - Zhang, Qianjie; He, Shaojing; Meng, Yicen; Yin, Tailang; Ming, Lei; Yang, Jing; Li, Saijiao (Frontiers in Endocrinology, 2024)
Background: For poor ovarian response (POR) population, the relationship between the medroxyprogesterone acetate (MPA) dose in progestin-primed ovarian stimulation (PPOS) and clinical outcome is still unclear. This study aims to explore the effect of MPA dose in PPOS on clinical outcomes in POSEIDON groups 3 and 4 patients with different body mass index (BMI), hoping to provide clinical doctors with better options for controlled ovarian hyperstimulation (COH) programs. Methods: Retrospective analysis of 253 oocyte retrieval cycles of POSEIDON groups 3 and 4 patients who underwent PPOS protocol in IVF/ICSI treatment in Reproductive Medical Center of Renmin Hospital of Wuhan University from March 2019 to April 2022. The effects of different MPA doses (8 mg/d or 10 mg/d) on pregnancy outcomes were compared in normal BMI (18.5 kg/m 2 -24 kg/m 2 ) and high BMI (≥ 24 kg/m 2 ) patients, and multivariate logistic regression analysis was performed to analyze the factors affecting pregnancy outcomes.Results: For normal BMI patients, 8 mg/d MPA group had a higher embryo implantation rate (33.78% vs. 18.97%, P = 0.012). For high BMI patients, 10 mg/d MPA group had a higher HCG positive rate (55.00% vs. 25.00%, P = 0.028), clinical pregnancy rate (50.00% vs. 20.00%, P = 0.025) and cumulative pregnancy rate (37.74% vs. 13.79%, P = 0.023) compared with 8 mg/d MPA group.There was no significant difference in cumulative live birth rate between the 8 mg/d and 10 mg/d MPA groups in patients with normal or high BMI.The results of multivariate logistic regression showed a significant correlation between MPA dose and cumulative pregnancy in high BMI population (OR = 0.199, 95% CI: 0.046~0.861, P = 0.031).Conclusion: For POR patients with high BMI, 10 mg/d MPA in PPOS protocol had a higher cumulative pregnancy rate than the 8 mg/d MPA, but had no significant effect on cumulative live birth rate.